Effect of fortification palm oil with some Egyptian spices on physico-chemical composition, microbiological analysis, sensory evaluation and economic study of Tallaga-like cheese - Hamad, Mohamed Nour-Eldin Farid; Taha, Eman Mamdouh; Mohamed, Walaa Mahmoud (Indian Journal of Dairy Science, 2017)
Four Egyptian spices (thyme, paprika, cumin and turmeric) with two different concentrations (20 and 50 g/kg) used for enrichment of palm oil with active compound to increase the oxidative stability, the antioxidant and antimicrobial activity for the oil and using for Tallaga-like cheese manufactured during the storage time (30 days) at 5°C. All fortified palm oil samples showed a good oxidative stability by rancimat measurements, and were good DPPH radical scavenger. Turmeric was the best among examined spices for both concentrations. The palm oil samples were prepared by treatment with 20g plant material/kg oil for 24h at 50°C, to be added in Tallaga-like cheese. The results showed that the highest values of pH, moisture, fat and TVFA values estimated in samples with all additions at zero time and decline significantly (p≤0.05) at 30 days. The highest number of TC was recorded at zero time and began to decline gradually at 30 days, on the other side, mould and yeast counts had significant effect on all treated cheese except for cheese with palm oil plus thyme (p=0.14), the maximum number was shown in cheese with palm plus cumin, while the minimum number was in cheese with palm oil only and plus turmeric. Concerning the sensory evaluation and economic analysis for cheese, the total scoring points were highly marked for cheese with control, followed by turmeric, thyme and paprika while cumin recorded the lowest score, samples also followed the same order for the lowest production costs.